2022
DOI: 10.1039/d2ta00579d
|View full text |Cite
|
Sign up to set email alerts
|

Biomass upgrading coupled with H2 production via a nonprecious and versatile Cu-doped nickel nanotube electrocatalyst

Abstract: Coupling oxidative biomass valorization with H2 production in a hybrid water splitting configuration is of significant importance to yield sustainable and value-added carbon products. Herein, we report an earth-abundant alloy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…The optimized catalyst in the coupling reaction showed a cell voltage (1.46 V) of 300 mV lower than that of water splitting (1.76 V) (Figure 8E) and delivers high‐evolution H 2 rate (41.2 L/(h m 2 )) and high FDCA yield (85.5 g/(h m 2 )) in alkaline electrolyte (Figure 8F). Excitingly, single‐metal ultrathin nickel hydroxide nanosheets (Ni(OH) 2 /NF), 19 Ni 2 P nanoparticle arrays (Ni 2 P NPA/NF), 120 and copper‐doped nickel nanotubes (NiCu NTs) have all been shown to possess excellent bifunctional catalytic activity of electrocatalytic HMF oxidation and hydrogen evolution 108 . Furthermore, the porous carbon‐coated MoO 2 –FeP heterojunction (MoO 2 –FeP@C) with abundant active interface exhibits a low overpotential of 103 mV at 10 mA/cm 2 for HER (Figure 8G–I).…”
Section: Coupling Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimized catalyst in the coupling reaction showed a cell voltage (1.46 V) of 300 mV lower than that of water splitting (1.76 V) (Figure 8E) and delivers high‐evolution H 2 rate (41.2 L/(h m 2 )) and high FDCA yield (85.5 g/(h m 2 )) in alkaline electrolyte (Figure 8F). Excitingly, single‐metal ultrathin nickel hydroxide nanosheets (Ni(OH) 2 /NF), 19 Ni 2 P nanoparticle arrays (Ni 2 P NPA/NF), 120 and copper‐doped nickel nanotubes (NiCu NTs) have all been shown to possess excellent bifunctional catalytic activity of electrocatalytic HMF oxidation and hydrogen evolution 108 . Furthermore, the porous carbon‐coated MoO 2 –FeP heterojunction (MoO 2 –FeP@C) with abundant active interface exhibits a low overpotential of 103 mV at 10 mA/cm 2 for HER (Figure 8G–I).…”
Section: Coupling Reactionsmentioning
confidence: 99%
“…Excitingly, single-metal ultrathin nickel hydroxide nanosheets (Ni(OH) 2 /NF), 19 Ni 2 P nanoparticle arrays (Ni 2 P NPA/NF), 120 and copperdoped nickel nanotubes (NiCu NTs) have all been shown to possess excellent bifunctional catalytic activity of electrocatalytic HMF oxidation and hydrogen evolution. 108 Furthermore, the porous carbon-coated MoO 2 -FeP heterojunction (MoO 2 -FeP@C) with abundant active interface exhibits a low overpotential of 103 mV at 10 mA/cm 2 for HER (Figure 8G-I). 32 The enhanced activity is attributed to the electron transfer from MoO 2 to FeP at the interface (Figure 8J), where electron accumulation on FeP helps to optimize the H 2 O and H* adsorption energies for HER, whereas hole accumulation on MoO 2 is beneficial for improving HMFOR activity.…”
Section: Coupling Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%
“…Cu-doped porous Ni nanotubes (NiCu NTs) with abundant active sites were exploited for the ECO of HMF with FDCA yields of approximately 100% and FE >90% during 5 consecutive cycles at 1.42 V vs. RHE. 96 Compared with NiCu NPs (27 mF cm −2 ) and Ni NPs (9 mF cm −2 ), NiCu NTs presented the enormous value of C dl (64 mF cm −2 ), suggesting that NiCu NTs were available with more active sites. However, in situ Raman showed that the in situ formed high-valent Ni 3+ OOH was the active species for ECO, and the role of Cu was unfortunately ignored.…”
Section: Electrocatalytic Oxidation Of Furansmentioning
confidence: 93%
“…include multiphase mixture, [12] single or double elements doping, [13][14][15][16][17][18] polymetallic oxides, hydroxides, and hydroxyl oxides [19][20] and special structure regulation. [21][22][23] The product with yields of about 99% and Faradaic efficiencies (FEs) of about 99% can be achieved on different catalysts.…”
Section: Introductionmentioning
confidence: 99%